The three dimensions of multimedia teaching of statistics - Nathaniel Derby; Wolfgang Härdle; Bernd Rönz (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
Statistics is often difficult for students, since it requires coordination of quantitative and graphical insights with mathematical ability. Furthermore, ever-increasing special knowledge of statistics is demanded, since data of increasing complexity and size need to be understood and analyzed. In the face of this changing demand on educated statisticians, our methods of teaching statistics is obsolete, continuing to rely on the blackboard, textbooks, and handwritten homework. With only these materials, it's impossible to teach some modern statistical techniques without confusing the student in a plethora of formulas and numbers. There is clearly a need for introducing more adaptive teaching methods to address this demand. In this article, we isolate three important dimensions of teaching statistics and propose how to map them onto a web-language-based computer teaching aid, called MM*STAT.
urn:nbn:de:kobv:11-10046642
Keywords: 330